English Speaking Anxiety of Vocational High School Students: Factors and Strategies to Cope With - Styfany, Gaby; Ririn Pusparini (The Future of Education Journal, 2025)
This study investigates the factors contributing to English speaking anxiety among vocational high school students, particularly in the hospitality department, and explores effective coping strategies. The purpose is to understand how psychological, social, and environmental factors influence students' reluctance to speak English and identify ways they manage their anxiety. Using a qualitative descriptive method, data were collected through questionnaires, semi-structured interviews, and classroom observations from 8 tenth-grade students at SMKN 1 Surabaya. Data analysis involved thematic coding to identify key anxiety factors and coping mechanisms. Findings revealed that fear of negative evaluation, communication apprehension, test anxiety, perceived low proficiency, and classroom environment significantly contribute to speaking anxiety. Students employ strategies like preparation, relaxation, positive self-talk, peer support, and resignation to cope. The results highlight the importance of supportive classroom settings and tailored interventions to reduce anxiety and improve speaking confidence. These findings contribute to the understanding of language anxiety in vocational contexts and suggest practical approaches for educators to facilitate effective communication skills development.